Fingerprint frontier: the evolution of biometric security - Khalifa, Othman Omran (Independently published, 2023)
The field of fingerprint biometrics is a cornerstone in the quest for accurate and efficient identity verification in today's growing landscape of security and identification technology. It have been used as a unique identifier for ages, but in our modern era, It have emerged as a cornerstone in the area of security and identity. This book offers a detailed trip into the intricate world of fingerprint biometrics, acting as a resource for professionals, hobbyists, and researchers interested in delving into this fascinating topic. This book acts as a compass to navigate the evolving landscapes of fingerprint biometrics and providing insights on the developments and innovations fueling the future. Each chapter acts as a portal, encouraging reader to explore the realms of fundamental understanding, advanced recognition algorithms, database administration complexities, and the numerous security problems that characterize the field of fingerprint biometrics. The book is divided into eight chapters, chapter One introduces fingerprint biometrics in general. Chapter two provides a detailed lens into the core mechanics, followed by an exploration of the algorithms that drive the matching processes in Chapter Three. Chapter Four delves into the essential topic of database maintenance, which is often overlooked but is critical to the effectiveness of fingerprint systems. The chapter then shifts to Chapter Five, which delves into the numerous "Security Challenges in Fingerprint Biometrics," recognizing the complexities and vulnerabilities in even the most secure systems. The sixth chapter is a moving meditation on "Privacy and Ethical Considerations in Fingerprint Biometric Systems." It sparks an important conversation on the ethical implications and privacy concerns embedded into the fabric of biometric technologies. Chapter Seven, "Best Practice in Fingerprint Security," emerges as a guiding light, delivering complete methods and procedures for developing and maintaining safe fingerprint systems, with a steadfast dedication to not simply identifying issues but also offering answers. Chapter Eight explores the unexplored territory of "Emerging Technologies in Fingerprint and its Security." Here, we look at the cutting-edge breakthroughs and future prospects that are ready to transform the biometric security scene.